Recycling waste from sawing MDF - Koval, Lyubomyr; Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2011)
Ways of using waste from cutting MDF and on the basis of this analysis scheme built their recycling, provides research data on the use of waste MDF, provides a process of linear elements of waste MDF.